PEMBUATAN APLIKASI MOBILE PEMBELAJARAN ADAB DAN DO’A MENGGUNAKAN METODE ADDIE - Abdul Rokhim; Siti Lailatul Rohmah (STMIK YADIKA BANGIL, 2020)
Abstract: Daily prayer is a prayer that can be practiced in daily life, the compilation will start or manage an activity. In general, conventional daily prayer learning is unattractive and unattractive, so that it can make children get bored / less focused on memorization. In addition, daily prayer lessons are also not equipped with manners materials for moral education for children from childhood. Therefore, the researchers developed a media application for learning etiquette and prayer that is applied to Android smartphones, so that it is easy for children to use and does not get bored quickly, so learning is presented in video and audio based applications. Application development uses the ADDIE method which has been used generally to develop multimedia applications, in applications that use the black box method, which results in clear video and audio, evaluation questions run well, and all menus are used well.Keywords: manners, prayer, ADDIE, blackbox, android